PENERAPAN ALGORITMA COLLISION DETECTION UNTUK PENYERANGAN NON-PLAYER CHARACTER (NPC) PADA GAME SOLO TANK - Syahrul Anwar , Muhammad; Mashuri , Chamdam (Inovate, 2024)
Non-player character attack strategy is one of the main requirements for creating a game. In carrying out attacks, special patterns are needed so that NPCs can carry out their roles properly and qualified tactics so that NPC don't lose quickly. one of the methods used for attacking non-player characters is Detection Collision. The use of Collision Detection can provide variations and conditions so that NPC can carry out attacks or other behaviors and with collision detection NPC will not mistakenly recognize which are enemies and which are friends. This study aims to apply the Collision Detection Algorithm to the Solo Tank game as an NPC attack scenario. The product in making this game is in the form of an Inter-Tank single-player Windows PC Game Application that can stimulate gamers' brain dexterity as well as with a 2.5D view and consists of 3 levels which make this game interesting to play, this game is played on a Windows-based PC or Laptop platform. Keywords: Strategy, NPC, Collision Detection, Game, Single Player.